2001
DOI: 10.1210/jcem.86.1.7159
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitogen-Activated Protein Kinase in Prostaglandin FAction in Human Granulosa-Luteal Cells1

Abstract: In the ovary it has been demonstrated that PGF(2alpha) activates the phospholipase C (PLC)/diacylglycerol/protein kinase C pathway. However, little is known about the downstream signaling events that mediate subsequent cellular responses such as steroidogenesis. The present study was designed to examine the effect of PGF(2alpha) on activation of the mitogen-activated protein kinase (MAPK) signaling pathway and its physiological role in human granulosa-luteal cells (hGLCs). Human GLCs, obtained from women under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The activation of PLC β could increase intracellular Ca 2+ [38], which is in line with this study that PLC activator increased the intracellular Ca 2+ concentration and PLC inhibitor decreased the intracellular Ca 2+ concentration. The PKC activator PLC could be activated by prostaglandin f (2alpha) in the ovary [39]. It was reported that the Wnt/Ca 2+ signaling pathway could reduce cisplatin resistance, and CaMKII might be an underlying therapeutic target in chemoresistant ovarian cancers [40].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of PLC β could increase intracellular Ca 2+ [38], which is in line with this study that PLC activator increased the intracellular Ca 2+ concentration and PLC inhibitor decreased the intracellular Ca 2+ concentration. The PKC activator PLC could be activated by prostaglandin f (2alpha) in the ovary [39]. It was reported that the Wnt/Ca 2+ signaling pathway could reduce cisplatin resistance, and CaMKII might be an underlying therapeutic target in chemoresistant ovarian cancers [40].…”
Section: Discussionmentioning
confidence: 99%
“…As for the regulation of PLC at the hormone level, scientific reports have shown that parathyroid hormone (PTH) could promote fracture healing and callus hardness in ovariectomized mice by increasing callus formation and reconstructing trabecular bone via a PLC‐independent pathway (Li, Yu, Huang, & Pang, ), and the activity of diapause hormone could be mediated through the Gαq‐PLC‐PKC cascade (Jiang et al, ). The binding of PGF2α to its receptor coupled to a PTX‐insensitive G protein could subsequently lead to PLC, PKC and MAPK activation (Tai, Kang, Choi, Tzeng, & Leung, ).…”
Section: Discussionmentioning
confidence: 99%